(untitled) (CIPEEX, 2025)
Swimming, with its growing popularity and professionalization, requires detailed physical preparation to optimize performance. This study aimed to investigate the importance of anthropometric profile during core muscle strengthening training in high-performance swimmers. A randomized study was conducted with an experimental group and a control group, involving athletes from the Evangelical Educational Association of Anápolis, aged between 10 and 22 years. The study included measurements of age, weight, height, BMI, wingspan, and foot size in three phases: pre-training, detraining, and post-training. Of the 28 athletes evaluated, 13 were in the Experimental Group and 15 in the Control Group. The analyses showed differences in anthropometric characteristics between the groups. Preliminary results suggest the need for further research on the correlation between anthropometric profile and core strengthening training. These data aim to support future investigations and training practices to improve swimmers’ performance.